Virtual Currencies and Beyond : Initial Considerations - He, Dong.; Habermeier, Karl.; Haksar, Vikram; Leckow, Ross. (Washington, D.C. : International Monetary Fund, 2016)
New technologies are driving transformational changes in the global financial system. Virtual currencies (VCs) and the underlying distributed ledger systems are among these. VCs offer many potential benefits, but also considerable risks. VCs could raise efficiency and in the long run strengthen financial inclusion. At the same time, VCs could be potential vehicles for money laundering, terrorist financing, tax evasion and fraud. While risks to the conduct of monetary policy seem less likely to arise at this stage given the very small scale of VCs, risks to financial stability may eventually emerge as the new technologies become more widely used. National authorities have begun to address these challenges and will need to calibrate regulation in a manner that appropriately addresses the risks without stifling innovation. As experience is gained, international standards and best practices could be considered to provide guidance on the most appropriate regulatory responses in different fields, thereby promoting harmonization and cooperation across jurisdictions.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet